Eosinopenia as a predictor of clinical outcomes in hospitalized patients with community-acquired pneumonia: A retrospective cohort study. - Wigdan Farah; Zhen Wang; Ognjen Gajic; Yewande E Odeyemi (PLoS ONE, 2025)
Eosinopenia has been reported as a predictor of unfavorable outcomes and a marker of severity in bacterial infections. We describe the association between eosinopenia and clinical outcomes in hospitalized patients with CAP. We conducted a retrospective study of hospitalized adult patients with community-acquired pneumonia at a large US academic medical center from January 2009 to December 2019. We collected data on patient demographics, disease severity, comorbidities, smoking history, inflammatory markers, blood eosinophil levels, mortality, length of hospital stay, and need for intensive care unit (ICU) or mechanical ventilation. According to blood eosinophil count, patients were grouped as eosinopenic (<50/μL) and non-eosinopenic (≥50/μL) based on prior studies. Analysis was performed using nonparametric Wilcoxon rank-sum test for continuous variables and the chi-square test for categorical variables. A logistic regression analysis with robust standard errors was used to assess the associations between eosinopenia and patient centered outcomes (in-hospital mortality, 30-day mortality, length of hospital stay, need for mechanical ventilation support, vasopressor support and ICU admission). Of the 3285 patients with CAP infection included in our analysis, 1304 (39.70%) were eosinopenic. Age, gender, race, and smoking status were similar between the two groups. The eosinopenic group had significantly higher inflammatory markers as measured by C-reactive protein (CRP), and higher disease severity scores., After adjusting for disease severity, chronic obstructive pulmonary (COPD), and CRP there was no significant difference in hospital mortality (odds ratio [OR] 2.16, 95% confidence interval [CI] 0.68-6.8), ICU admission (OR: 1.21, 95% CI: 0.83-1.79), invasive and non-invasive ventilatory support (OR: 1.21, 95% CI: 0.52-2.81). Contrary to previously published data, our analysis did not demonstrate an association between eosinopenia and increased mortality risk in hospitalized patients with CAP highlighting the complexity of CAP prognosis.